A case of hepatic-splenic abscess in a non-endemic area of brucellosis: insights from complex infection with brucellosis - Shufang Pan; Yuankai Wu; Kaixiang Zhou; Jie Gao; Jiaoling Li; Chengyuan Liu; Yutian Chong; Jianyun Zhu (BMC Infectious Diseases)
Abstract We present the case of a 47-year-old male patient who exhibited recurrent fever and was diagnosed with liver and splenic abscesses. Magnetic Resonance Imaging of the upper abdomen showed several hypodense lesions in the liver and spleen. A puncture of the liver abscess was performed and the sample was subjected to Next-Generation Sequencing (NGS). The results of both the liver sample and blood NGS indicated the presence of Brucella. Further examination of the liver and spleen pus suggested necrotizing purulent inflammation. Consequently, the final diagnosis confirmed the condition as brucellosis, liver abscess, and splenic abscess. Doxycycline, rifapentine, and levofloxacin were administered to treat the infection. However, the results were suboptimal. Subsequently, the patient underwent a splenectomy and open drainage of an abscess of the liver. Following the surgical intervention, the patient's symptoms improved gradually and he continued his regimen of doxycycline, rifapentine, and trimethoprim-sulfamethoxazole therapy. This triple-drug combination was maintained for a duration of up to 32 months to effectively control the infection and was ultimately discontinued after a thorough evaluation of the stable lesion. For brucellosis patients with abdominal abscesses, effective treatment requires surgical debridement and extended anti-infective therapy.